Nauczanie religii w polskich szkołach – sukces czy porażka? - Jedynak, Witold (Poznańskie Studia Teologiczne, 2018)
Religious Education was reintroduced to state Polish schools in September 1990. The par- ticipation is not obligatory and it depends on parents and pupils. Sociological studies show that Religious Education has far more supporters than opponents which, undoubtedly, is the pastoral success of the Catholic Church. Despite the fact that in the last few years the attendance at RE was dropping, the vast majority of pupils still participate in it. Young people assess the quality of RE in a positive way. Some of them think that RE is interesting and they participate in it willingly. Others are of the opinion that RE is no di erent from other subjects. For the Catholic Church Religious Education is an important pastoral task. Therefore, it under- takes activities in order to provide quali ed RE teachers. The drawback of this e ort is, undoubte- dly, the fact that the catechization at school is done by laypeople with the simultaneous pullback of priests. Both pupils and parents are of the opinion that such actions not only impair the quality of RE teaching and lead to poor participation but also damage the relation between young people and parishes. In times when the level of religiosity and morality is falling, the Church should intensify its e ort to stop the process of secularization of young generation and strengthen or even rebuild the relation between young people with local Church communities by providing e ective RE teaching.